Bureaucrats and Leadership
XIV, 225 p.
Keywords: The book uses a biographical approach to analyse the potential for, forms of, and constraints upon bureaucratic leadership in modern government. Case studies, written by experts in the different fields, assess the impact of particular officials operating in Whitehall, the United States federal government, the health service, local government, and Europe. The book brings together an innovative methodology with a wide policy coverage.